2008
DOI: 10.1051/dst:2007008
|View full text |Cite
|
Sign up to set email alerts
|

Powder agglomeration during the spray-drying process: measurements of air properties

Abstract: -Instant food powders are usually produced by spray drying of formulated liquid and powder agglomeration, either into the drying chamber or in an external fluid bed. During spray drying, according to the liquid composition, the viscosity of the initial liquid drops increases more or less rapidly, until the drop surface reaches a rubbery state considered as sticky, before further drying. This sticky property may be used to produce agglomerates inside the chamber by adding dry solid particles, as fines. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 11 publications
(11 reference statements)
1
14
0
Order By: Relevance
“…Gianfrancesco et al . () also found that spray drying at a low inlet air temperature and high feed flow rate led to an infant food powder that still had high moisture content. The mathematical expression of relationship between the response and spray drying variables is shown below: Y1=38.19930.1261X10.0537X3+0.0004X1 2+0.0386X2 2+0.0001X3 2 …”
Section: Resultsmentioning
confidence: 91%
“…Gianfrancesco et al . () also found that spray drying at a low inlet air temperature and high feed flow rate led to an infant food powder that still had high moisture content. The mathematical expression of relationship between the response and spray drying variables is shown below: Y1=38.19930.1261X10.0537X3+0.0004X1 2+0.0386X2 2+0.0001X3 2 …”
Section: Resultsmentioning
confidence: 91%
“…Patel et al (2009) reported that higher inlet air temperatures result in faster moisture evaporation in spray dryers. When identifying operating conditions in which particles are sticky, Gianfrancesco et al (2008) reported that a low inlet air temperature (144°C) and high liquid flow rate (75 mL min )1 ) lead to a final powder with a high MC (>8%). Figure 4 shows the interaction effects of inlet air temperature (X 1 ), feed flow rate (X 2 ) and air flow rate (X 3 ) on the MC of samples.…”
Section: Moisture Contentmentioning
confidence: 99%
“…Air water contents Y inside the chamber were determined from measured T and RH according to the enthalpic diagram of humid air. Detailed experimental results are reported elsewhere (Gianfrancesco et al 2008(Gianfrancesco et al , 2009). …”
Section: Spray Drying Trialsmentioning
confidence: 99%